Acute effects of combined lower-body high-intensity interval training and upper-body strength exercise on explosive strength performance in naturally menstruating women - Feuerbacher, J. F.; Dragutinovic, B.; Jacobs, M. W.; Schumann, M. (International Journal of Sports Physiology and Performance, 2023)
We aimed at investigating the acute effects of lower-body high-intensity interval training (HIIT) on upper- and lower body explosive strength assessed by mean propulsive velocity (MPV) in naturally menstruating women. In addition, we assessed the combination of lower-body HIIT and squat, as well as lower-body HIIT and bench press, on bench press and squat MPV. Methods: Thirteen women (age: 23 [2] y, menstrual cycle length: 28.4 [2.0] d) completed 2 training modalities on separate days (separated by 30 [4.2] d) consisting of HIIT followed by lower-body (HIIT + LBS) or upper-body (HIIT + UBS) strength loading. Squat and bench press MPV were assessed before HIIT (T0), after HIIT (T1), after the strength loading (T2), and 24 hours postloading (T3). Results: Mixed factorial analysis of variance indicated a significant effect for time in bench press and squat (P < .001) but not for interaction. Pairwise comparison showed that bench press MPV remained unchanged (P = 1.000) at T1 but was reduced at T2 compared with T0 (HIIT + LBS: -8.2% [3.9%], HIIT + UBS: -13.8% [12.1%], P < .001) and T1 (HIIT + LBS: -7.1% [3.2%], HIIT + UBS: -12.7% [8.7%], P < .001). Squat MPV decreased at T1 (HIIT + LBS: -6.0% [8.8%], HIIT + UBS: -4.8% [5.4%], P = .009) and was found to be decreased at T2 compared with T0 in both conditions (HIIT + LBS: -6.9% [3.3%], HIIT + UBS: -7.4% [6.1%], P < .001) but not compared with T1 (P = 1.000). Bench press and squat MPV returned to baseline at T3 compared with T0 (P > .050). Conclusion: Lower- but not upper-body explosive strength was reduced by HIIT. HIIT combined with upper- or lower-body strength loading resulted in a reduction of squat and bench press explosive strength.